Genomic Analysis Indicates the Presence of an Asymmetric Bilayer Outer Membrane in Planctomycetes and Verrucomicrobia - Speth, Daan R.; van Teeseling, Muriel; Jetten, Mike (Frontiers in Microbiology, 2012)
Bacteria of the phylum Planctomycetes are of special interest for the study of compartmental cellular organization. Members of this phylum share a very unusual prokaryotic cell plan, featuring several membrane-bound compartments. Recently, it was shown that this cellular organization might extend to certain members of the phylum Verrucomicrobia. The Planctomycete cell plan has been defined as featuring a proteinaceous cell wall, a cytoplasmic membrane surrounding the paryphoplasm and an intracytoplasmic membrane defining the riboplasm. So far it was presumed that Planctomycetes did not have an asymmetric bilayer outer membrane as observed in Gram-negative bacteria. However, recent work on outer membrane biogenesis has provided several marker genes in the outer membrane protein (OMP) assembly and the lipopolysaccharide (LPS) insertion complexes. Additionally, advances in computational prediction of OMPs provided new tools to perform more accurate genomic screening for such proteins. Here we searched all 22 Planctomycetes and Verrucomicrobia genomes available in Genbank, plus the recently published genome of ‘Candidatus Scalindua profunda’, for markers of outer membrane biogenesis and OMPs. We were able to identify the key components of LPS insertion, OMP assembly and at least eight OMPs in all genomes tested. Additionally, we have analyzed the transcriptome and proteome data of the Planctomycetes ‘Candidatus Kuenenia stuttgartiensis’ and ‘Ca. S. profunda’ and could confirm high expression of several predicted OMPs, including the biomarkers of outer membrane biogenesis.